Influencias de las estrategias metodológicas activas, en el área de lengua y literatura y su relación en la comprensión lectora, en los estudiantes de quinto, año de educación básica del centro educativo “Salvador Bustamante Celi” de la Comunidad San Pablo de Gramapamba, parroquia Matríz, Canton Guamote, provincia de Chimborazo, periodo 2010-2011. - Malán Valente, Rebeca (2011)
Dear reader, please find the following paper entitled "Methodological Strategies Active in the Area of Language and Literature and its relation to reading comprehension, students in fifth, year of Basic Education Educational Centers" Salvador Bustamante Celi "community San Pablo de Gramapamba, Matrix Parish, Canton Guamote, Chimborazo Province, period 2010-2011. Thus justification is a community that has had more prominence in recent years within the province of Chimborazo, without a doubt the inhabitants of the special population students Intercultural Bilingual Community Education Center (CECIBs) "Salvador Bustamante Celi "have many flaws in the special inter-language learning and literature, hence our theme is active methodological strategies for the area of language arts in children of Basic education fifth year with the aim of improving and implementing new active-learning methodologies for teachers. Variables are identified as V1, V2 active methodologies strategies: reading in children, for which they are based on the operationalization of variables according to the reality of the difficulty. As in chapter two scientific theory and Clarice helps determine the good or bad implementation of active methods for reading and all its effects, among other causes as well as in the legal framework helps to ensure with the studies and our work grade according to the articles of the law on higher education; Credit blended format, for which is accompanied by intercultural education law, within the conceptual theory find specific knowledge of what is active teaching tion students. As in my work could not miss the referential theory where we have to know the location of the school rather Salvador Bustamante Celi Guamote-Matrix, to the west of the province of Chimborazo. Without doubt one of the problems of most concern to teachers of any level is that of reading XIII comprehension, often wonder how to teach students to understand what they read. Thus, in many studies are currently underway related to this problem, in this research work we have analyzed to determine whether the methodological strategies used in language and communication classes affect students' reading comprehension, for which it was made A study in children fifth year of Basic Education of the Community Education Center Salvador Bustamante Celi community Gramapamba San Pablo, parish Guamote district, province of Chimborazo during the academic year 2010.2011. Our proposal entitled "Methodological INFLUENSE THE ESTRATEGUIAS ACTIVE IN THE AREA OF LANGUAGE AND LITERATURE AND ITS RELATION TO THE READER CONPRENCION FIFTH YEAR STUDENTS OF BASIC EDUCATION" in order to promote the knowledge of teachers and students loess very particular el Quinto years basic education, to strengthen a better learning, for he has evidence a report that found the signatures of Mr. Director of the center, planning, photographs and other, therefore we are very pleased to have done our research and implementation of our proposal.